2012
DOI: 10.2308/accr-50193
|View full text |Cite
|
Sign up to set email alerts
|

Is U.S. Multinational Dividend Repatriation Policy Influenced by Reporting Incentives?

Abstract: This study finds evidence that public-company reporting by U.S. multinational corporations (MNCs) creates disincentives to repatriate foreign earnings to the U.S. and contributes to the accumulation of cash abroad. MNCs operate under U.S. international tax laws and financial reporting rules and face two potential consequences when they repatriate foreign earnings: a cash payment for repatriation taxes and a reduction in reported accounting earnings. Using a confidential dataset of financial and operating chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 45 publications
4
49
2
Order By: Relevance
“…6 The US, South Korea, and Mexico remain the only major countries outside Europe using the worldwide tax system. This tax system has been criticized for its adverse impact on U.S. firms' competitiveness vis-à-vis multinationals headquartered in territorial tax system jurisdictions because of the additional tax burdens imposed on repatriated profits (Hines, 2006;Hubbard, 2006), and because it encourages firms to "park" profits generated from foreign operations outside their home country (Blouin et al, 2012 Another important home-country characteristic examined is the impact of conformity between financial reporting and tax reporting on effective tax rates. 8 Examples of financial and tax reporting conformity include: (i) the use of financial accounting regulations for tax estimation or vice-versa; and (ii) the use of tax provisions for specified items in both the financial statements and the tax returns (Lamb, Nobes, & Roberts, 1998;Shackelford & Shevlin, 2001).…”
Section: Development Of Hypothesesmentioning
confidence: 99%
“…6 The US, South Korea, and Mexico remain the only major countries outside Europe using the worldwide tax system. This tax system has been criticized for its adverse impact on U.S. firms' competitiveness vis-à-vis multinationals headquartered in territorial tax system jurisdictions because of the additional tax burdens imposed on repatriated profits (Hines, 2006;Hubbard, 2006), and because it encourages firms to "park" profits generated from foreign operations outside their home country (Blouin et al, 2012 Another important home-country characteristic examined is the impact of conformity between financial reporting and tax reporting on effective tax rates. 8 Examples of financial and tax reporting conformity include: (i) the use of financial accounting regulations for tax estimation or vice-versa; and (ii) the use of tax provisions for specified items in both the financial statements and the tax returns (Lamb, Nobes, & Roberts, 1998;Shackelford & Shevlin, 2001).…”
Section: Development Of Hypothesesmentioning
confidence: 99%
“…In addition, prior studies have found a negative association between repatriations from foreign subsidiaries of U.S. MNCs and the estimated U.S. repatriation tax cost (Hines and Hubbard [1990]; Altshuler and Newlon [1993]; Desai et al [2001]; Desai et al [2007]) and between repatriations and financial reporting incentives (Blouin et al [2012] Graham et al [2010]). Altshuler, Newlon, and Randolph (1995) attempt to differentiate the effects of permanent and transitory components of the U.S. tax cost of repatriations on U.S. MNCs' repatriation decisions.…”
Section: Firms' Repatriation Decisionsmentioning
confidence: 99%
“…By designating foreign earnings as permanently reinvested, 3 firms are able to report higher after-tax net income in their financial statements. Existing research provides evidence the U.S. tax and financial reporting treatment of foreign earnings impacts some U.S. MNCs' repatriation decisions (Hines and Hubbard [1990]; Altshuler and Newlon [1993]; Desai, Foley, and Hines [2001]; Desai, Foley, and Hines [2007]; Graham, Hanlon, and Shevlin [2011]; Blouin, Krull, and Robinson [2012]). …”
Section: Introductionmentioning
confidence: 99%
“…Likewise, taxation regimes in play typically discourage US multinationals from repatriating foreign earnings. As such, cash tends to accumulate overseas (Blouin, Krull & Robinson, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%